WHAT TEACHERS NEED; CARRYING OUT ISLAMIC BASED DIGITAL LITERACY ASSESSMENT THROUGH THE PROJECT - Nazriani Lubis; Alkausar Saragih; Asnarni Lubis (LP2M UMN AL WASHLIYAH, 2020)
The community service program focuses on improving senior high school teachers’ ability in carrying out Islamic-based digital literacy assessment through Project-based Learning. It is empirically revealed by the research that Project-based Learning with video project serves considerable benefits, specifically, it leads to Islamic-based digital literacy assessment. The reality shows that teachers of MTS.Swasta Lab IKIP Al Washliyah located in Medan Amplas have never experienced digital literacy assessment journey since they tend to apply silent reading, and memorizing. Through this program, the teachers are comprehensively trained to implement, to design, to innovate the video project linking to Islamic values in which all values experienced by students are assessed based on digital literacy skill with available online application. Therefore, the assessment of Islamic-based digital literacy is carried out to gather the information of students’ process (reading, writing, and applying online digital tools) rather than scoring or numbers. Based on analysis, it is found that most teachers strongly agree with program that can be seen from six indicator achieved. It implies that it becomes challenging, yet authentic in involving teacher to have digital journey, particularly, in new normal era.